Deposition of GeSn film on Si substrate by plasma-enhanced chemical vapor deposition using GeCl4 and SnCl4 in H2 for developing short-wave infrared Si photonics. (1st August 2023) - Yang, Tzu-Hung; Lin, Zhe-Zhang; Tsai, Shang-Che; Dai, Jia-Zhi; Chen, Shih-Ming; Lin, Ming-Wei; Chen, Szu-yuan
Abstract: The deposition of a GeSn film on Si substrate with GeCl4 and SnCl4 in H2 as precursors was demonstrated by using plasma-enhanced chemical vapor deposition (PECVD). A partially strain-relaxed, impurity-free, monocrystalline GeSn film with a surface roughness of 6 nm and a threading-dislocation density of 1 × 10 7 cm −2 could be directly grown at a rate of ca. 15 nm/min at a substrate temperature of 180 °C without the need of a buffer layer or post-annealing. A Sn atomic percentage exceeding 9% was achieved, providing a light absorption beyond 2 . 4 μ m for the deposited 260-nm-thick film. The same deposition process for Ge and Sn enabled easier control of film deposition conditions and better clarification of the underlying mechanisms. The low deposition temperature renders this method compatible with complementary metal–oxide–semiconductor (CMOS) technology, suitable for developing short-wave infrared Si photonics. Highlights: GeSn is deposited on Si substrate by PECVD with GeCl4 and SnCl4 in H2 . Epitaxially-grown monocrystalline GeSn film with mild compressive strain is obtained. Low threading-dislocation density and >9% Sn percentage are achieved. GeSn film is grown at low substrate temperature without need of post-annealing. The technique is suitable for developing short-wave infrared Si photonics.